Why Is the U.S. Preterm Birth Rate So Much Higher Than the Rates in Canada, Great Britain, and Western Europe?. (October 2018) - Bronstein, Janet M.; Wingate, Martha S.; Brisendine, Anne E.
The portion of newborns delivered before term is considerably higher in the United States than in other developed countries. We compare the array of risk exposures and protective factors common to women across national settings, using national, regional, and international databases, review articles, and research reports. We find that U.S. women have higher rates of obesity, heart disease, and poor health status than women in other countries. This is in part because more U.S. women are exposed to the stresses of racism and income disparity than women in other national settings, and stress loads are known to disrupt physiological functions. Pregnant women in the United States are not at higher risk for preterm birth because of older maternal age or engagement in high-risk behaviors. However, to a greater extent than in other national settings, they are younger and their pregnancies are unintended. Higher rates of multiple gestation pregnancies, possibly related to assisted reproduction, are also a factor in higher preterm birth rates. Reproductive policies that support intentional childbearing and social welfare policies that reduce the stress of income insecurity can be modeled from those in place in other national settings to address at least some of the elevated U.S. preterm birth rate.